2018
DOI: 10.9744/ijbs.1.2.57-62
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Personality Types and Demographic Factors on Overconfidence Bias and Decision Making of Investment Types

Abstract: In financial management theories an investor will act rationally and make a desicion to invest based on the rules in the financial management theory. Nevertheless, in reality the decision making to invest is very often irrational and not in accordance with the financial management theory. This deviation is caused by the bias of investors’ behaviour in making a decision. Investors who only focus on the return of an investment without paying attention to the risks are said to experience overconfidence bias. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
2
5
1
Order By: Relevance
“…In this study overconfidence is proven to be a predictor of investment decisions. The results of this study support the results of research by Armansyah (2021) that overconfidence has proven to be a predictor of investment decisions by capital market investors and also supports and Nofsinger (2016), Khan et al (2017), Tjandrasa and Tjandraningtyas (2018), and Qasim et al (2019. This is possible, confidence is needed in making investment decisions in the capital market because every decision taken has risks. Every investment decision requires confidence from investors to make a decision but overconfidence will also lead to disaster.…”
Section: Inner Modelsupporting
confidence: 87%
See 1 more Smart Citation
“…In this study overconfidence is proven to be a predictor of investment decisions. The results of this study support the results of research by Armansyah (2021) that overconfidence has proven to be a predictor of investment decisions by capital market investors and also supports and Nofsinger (2016), Khan et al (2017), Tjandrasa and Tjandraningtyas (2018), and Qasim et al (2019. This is possible, confidence is needed in making investment decisions in the capital market because every decision taken has risks. Every investment decision requires confidence from investors to make a decision but overconfidence will also lead to disaster.…”
Section: Inner Modelsupporting
confidence: 87%
“…This is interesting because this behavioral bias can lead to a crisis in a country (Armansyah, 2018) or even when the Covid-19 pandemic conditions affect the capital market (Allam et al, 2020). Several studies have found that overconfidence, endowment bias, confirmation bias, and recency bias all have a significant impact on investment decisions (Tjandrasa & Tjandraningtyas, 2018;Peñón & Ortega, 2018;Qasim et al, 2019;Rudiawarni et al, 2020;Rabbani et al, 2021;Armansyah, 2021;Gavrilakis & Floros, 2022). The purpose of this research is to gather evidence of irregularities in financial behavior such as herd instinct bias, emotional bias, and information processing bias in investment decision making as information technology and communication media evolve, as well as new policies in the Indonesian capital market.…”
Section: Figure 1 Growth Of Indonesian Capital Market Investorsmentioning
confidence: 99%
“…Agreeableness: Investors of this personality type are less likely to choose risky investment options (Pak & Mahmood, 2015;Tjandrasa & Tjandraningtyas, 2018). Agreeableness personality decreases the risk-taking propensity (Markey, Markey, Ericksen & Tinsley, 2006;Nicholson et al, 2005;Anic, 2007;Deck et al, 2008;Durand et al, 2008;Pinjisakikool, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Openness: Openness is positively related with investor's risk tolerance behavior (Zhuan et al, 2016;Pan & Statman, 2013;Kowert & Hermann, 1997;Pak & Mahmood, 2015). Investors of this personality type are more likely to choose risky investment options (Durand et al, 2008;Ali & Waheed, 2013;Tjandrasa & Tjandraningtyas, 2018). This personality increases the risk-taking propensity (Nicholson et al, 2005;Deck et al, 2008;Anic, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Overconfidence is a common bias among investors that makes them very confident in their expertise, which leads to ignoring investment risks (Kumar & Goyal, 2015). Overconfidence bias is a problematic issue when making an investment decision because of the potential for financial losses (Tjandrasa & Tjandraningtyas, 2018). Uncertainty is an essential factor affecting overconfidence (Ancarani et al, 2016).…”
Section: H5mentioning
confidence: 99%